The inclusive school of collective learning - Gbêhi, Clément; VODOUHE, Simplce D.; GBEHI, Hariane N. (European Journal of Applied Sciences, 2021)
How women actually are collectively learning new knowledge in practice, and the constraints they are experiencing? Based on an analysis of three contrasted small scale cassava processing cooperatives, this article traced how women allow and mediate emerging critical events when applying new measures and collectively learned about, by analyzing archives data, following and interviewing; and observing in real time those who are closely involved in collective learning processes. Evidence proves that collective learning women were experiencing with the traditional system of cassava processing have taken a new translation with the promotion of two days of cassava processing (instead of six or seven days traditionally assigned in cassava processing) and the use of improved garifyers. However, important critical challenges emerged. These are economic, technical and political support. Mediating these challenges did not pose serious problems since women deployed ideas and assembled social representations relevant to enforce arrangements. Collective learning then entails consideration and incorporation of the local socio-cultural models during the application of the new measures, and which require to be merged with emerging critical challenges. Further data analysis prove how women collectively change strategies that governed the puzzle of their life vis-a-vis cassava processing; and on the basis of which they considered emerging challenges and applied solutions.